Directors in the Loop? Responsible Corporate Governance for the Era of AI - Warneke, Lynn (2024)
The relationship between corporate success and technological progress has never been more overt, with digital businesses and products proliferating at extraordinary pace and scale. Of the many innovations to have emerged, Artificial Intelligence (AI) entails arguably the greatest disruption to the corporation, economy, law and society, and thus represents a singular challenge for the company director. AI is becoming pervasive, driving profitability and competitive differentiation, yet its profound socioeconomic externalities are provoking attention on corporate governance and the nexus between private value and public interest. At the same time, a lack of contextualisation for AI in contemporary regulatory frameworks creates ongoing legal uncertainties for industry and society. This paper critically assesses the effectiveness of corporate law and governance in this context, and argues—primarily from the Australian perspective—that directors are not adequately prepared to govern AI for long-term corporate value. Part 1 descriptively examines the distinctive challenge of AI governance, contextualising the subsequent normative arguments. Part 2 critically analyses present-day board and legal effectiveness in the governance of AI for shareholder and stakeholder benefit. Part 3 explores “responsible AI” governance reforms, contending substantial legal and normative changes are required in future. AI will effect a momentous socioeconomic transformation, promising great benefits but carrying equally profound risks; therefore, the paper concludes that while an appropriate regulatory framework for AI is now essential, the director has a critical role to pre-emptively adopt “corporate techno-social responsibility” principles and establish a new model of responsible governance to redefine corporate value for this most disruptive era.